2012
DOI: 10.1007/s00464-012-2323-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery for palliative resection of the primary tumor in incurable stage IV colorectal cancer

Abstract: A laparoscopic procedure should be considered for palliative resection of the primary tumor for incurable stage IV colorectal cancer, because the results of this study indicate that the procedure is safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
2
15
1
Order By: Relevance
“…The median age of the patients in all studies was 67.1 (59–80) years and was similar to the open colectomy group reported in five studies of 64 (62–68) years . The male/female ratio reported in 10 studies was similar in both groups (639/419 open; 600/509 laparoscopic). Only three studies reported T‐stage , and three reported ASA grade .…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…The median age of the patients in all studies was 67.1 (59–80) years and was similar to the open colectomy group reported in five studies of 64 (62–68) years . The male/female ratio reported in 10 studies was similar in both groups (639/419 open; 600/509 laparoscopic). Only three studies reported T‐stage , and three reported ASA grade .…”
Section: Resultssupporting
confidence: 76%
“…The most common procedure was right hemicolectomy and the median duration of follow‐up reported from five studies was 17 (13–72) months . The median age of the patients in all studies was 67.1 (59–80) years and was similar to the open colectomy group reported in five studies of 64 (62–68) years . The male/female ratio reported in 10 studies was similar in both groups (639/419 open; 600/509 laparoscopic).…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations